2007
DOI: 10.1016/j.otohns.2006.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Radical surgery: Effect on quality of life and pain in chronic rhinosinusitis

Abstract: Radical surgery improves the physical burden of chronic rhinosinusitis and pain experience in patients with therapy resistant chronic rhinosinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
(36 reference statements)
0
23
0
1
Order By: Relevance
“…Videler et al ., administering the Short-Form health survey (SF-36), found that patients with CRS had significantly worse QoL scores than patients with other chronic conditions, including head and neck cancer, hypertension, angina pectoris, and migraine22. Interestingly, Ottaviano et al .…”
Section: Discussionmentioning
confidence: 99%
“…Videler et al ., administering the Short-Form health survey (SF-36), found that patients with CRS had significantly worse QoL scores than patients with other chronic conditions, including head and neck cancer, hypertension, angina pectoris, and migraine22. Interestingly, Ottaviano et al .…”
Section: Discussionmentioning
confidence: 99%
“…The idea of removing all involved bone, through drilling and the performance of radical procedures (Denker [19], endoscopic modified Lothrop or Draf 3 [20]), is an attractive one. There is some evidence that an endonasal medical maxillectomy (Denker) may improve the outcome in patients with recalcitrant CRS [19].…”
Section: Surgerymentioning
confidence: 99%
“…There is some evidence that an endonasal medical maxillectomy (Denker) may improve the outcome in patients with recalcitrant CRS [19]. However, its role -if any -in patients with osteitis is less well defined.…”
Section: Surgerymentioning
confidence: 99%
“…Kerrebijn et al performed it in 56 patients and reported relief of sinusitis with significant improvement in symptoms 13. Videler et al78, 79 reported significant improvements in symptoms and quality‐of‐life measures from Denker's procedure, and Wreesmann et al80 reported improvement of lower airway symptoms in asthmatic patients. Both suggested that radical surgery should be an option for patients who fail repetitive conservative functional surgery 78, 80…”
Section: Introductionmentioning
confidence: 99%